Indirect effects of PTSD and complex PTSD in the relationship of polyvictimization with intimate partner violence victimization and perpetration among men in mandated treatment. Issue 1 (31st December 2020) - Gilbar, Ohad; Ford, Julian
ABSTRACT: Background: Polyvictimization is associated with posttraumatic stress disorder (PTSD), severe impairment, and re-victimization, including due to intimate partner violence (IPV), but polyvictmization's role in the perpetration of IPV is less clear. Objective : To examine the indirect effect of PTSD and complex PTSD in the relationship between polyvictimization and IPV perpetration. Method : Polyvictims were identified by cluster analysis of self-reported lifetime victimization history data in a random national sample ( N = 234) of men at 66 clinical treatment centers for domestic violence perpetrators in Israel. Results : Four sub-groups were identified: low exposure to abuse and physical neglect (C1, N = 105), and three polyvictim sub-groups characterized by multiple forms of past exposure to neglect and verbal abuse (C2, N = 38), to verbal and physical abuse without neglect (C3, N = 46), or to neglect and both verbal and physical abuse (C4, N = 28). Participants also were characterized as having low exposure to traumatic events across the lifespan (cluster L5, N =156), or high exposure to traumatic events across the lifespan (cluster L6, N =78). Complex PTSD symptoms had an indirect effect in the relationship between membership in the C3 and C4 polyvictimization clusters (β=.45, p <.05, β=.60, p <.05; respectively) and severity of psychological IPV victimization, as well as between C3 polyvictimization cluster membership and severity of psychological IPV perpetration (β=.32, p <.05). In contrast, PTSD symptoms had no indirect effect in any relationship between cluster membership and IPV outcomes. High lifetime trauma exposure also was directly associated with sexual IPV victimization. Conclusions : Complex PTSD may be a mechanism linking polyvictimization to the severity of both IPV victimization and perpetration. Clinical implications are discussed. Abstract : HIGHLIGHTS: Complex PTSD symptoms, but not PTSD's traditional symptoms, may be a link between childhood 75 polyvictimization and interpersonal partner violence (IPV) victimization and perpetration among men mandated for IPV 80 treatment. Additionally, high lifetime trauma exposure, may increase these men's risk of being a victim of sexual IPV.